Revisión jurídica y jurisprudencial de la consulta previa y su aplicación en el Norte del Cauca (2007)
Cali de Lat: 03 24 00 N degrees minutes Lat: 3.4000 decimal degrees Long: 076 30 00 W degrees minutes Long: -76.5000 decimal degrees.